2017
DOI: 10.1007/s12551-017-0316-0
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and biochemical strategies to understand membrane binding and pore formation by sticholysins, pore-forming proteins from a sea anemone

Abstract: Actinoporins constitute a unique class of poreforming toxins found in sea anemones that are able to bind and oligomerize in membranes, leading to cell swelling, impairment of ionic gradients and, eventually, to cell death. In this review we summarize the knowledge generated from the combination of biochemical and biophysical approaches to the study of sticholysins I and II (Sts, StI/II), two actinoporins largely characterized by the Center of Protein Studies at the University of Havana during the last 20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 103 publications
(227 reference statements)
0
8
0
Order By: Relevance
“…The increase in surface pressure (Δπ) by the association of peptides with previously formed lipid monolayers at the air-water interface can be employed to characterize their ability to interact with organized lipids (17,48,61). This method has the advantage that it does not require fluorescent amino acids or probes to detect peptide-lipid interactions, thus complementing fluorescence based lipid binding assays (62).…”
Section: Iii4 Stii1-30 Activity In Membrane Systems Is Enhanced By Pementioning
confidence: 99%
“…The increase in surface pressure (Δπ) by the association of peptides with previously formed lipid monolayers at the air-water interface can be employed to characterize their ability to interact with organized lipids (17,48,61). This method has the advantage that it does not require fluorescent amino acids or probes to detect peptide-lipid interactions, thus complementing fluorescence based lipid binding assays (62).…”
Section: Iii4 Stii1-30 Activity In Membrane Systems Is Enhanced By Pementioning
confidence: 99%
“…The present study showed the identification of a pore-forming protein in the A. dowii venom. Among proteins previously described in sea anemones to have pore-forming capacity, actinoporins stand out owing to their proven ability to form pores in the cell membrane, which are directly responsible for osmotic imbalance and cell death [15,58]. The membrane-binding activity of actinoporins depends on the lipid composition, while a high concentration of sphingomyelin has been proven to facilitate pore formation [24,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Among PFTs, APs have aroused the interest of the scientific community due to their biomedical or biotechnological potential to build immunotoxins [ 12 , 13 , 14 ], vaccine platforms [ 7 , 8 ], and nanopore-based biosensors [ 15 , 16 , 17 ]. Fragaceatoxin C (FraC) produced by Actinia fragacea [ 18 , 19 ], equinatoxin II (EqTII) from Actinia equina [ 20 , 21 ] and sticholysins (Sts), I (StI), and II (StII) purified from Stichodactyla helianthus [ 22 , 23 , 24 , 25 ] are the most extensively studied toxins in this family. APs exist as isoforms in most sea anemones which exhibit diverse pI, molecular weight, and piercing activity.…”
Section: Actinoporins Are Potent Toxins Produced By Sea Anemonesmentioning
confidence: 99%